PENGARUH KEPERCAYAAN DIRI TERHADAP INTERAKSI SOSIAL SISWA KELAS X SMK SWASTA PANCA BHAKTI KUBU RAYA - Muniroh, Siti; Asrosi, Asrosi; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Social interaction is the key of all social life, because without social interaction there may be no life together. In order to make the individuals are able to interact socially well, somebody must have high confidence in order to make it easier in interacting with other individuals. Confidence is also needed to be more self-respecting, because it is built on the basis of a positive feeling of your own self-respect. The general purpose of this study was to describe the influence of self-confidence to the social interaction of 10th grade students of Panca Bhakti Vocational High School Kubu Raya.Â The population in this study was 146 students and the sample was 59 students at the tenth grade of Panca Bhakti Vocational High School Kubu Raya. This study used quantitave approach. The techniques in collecting data used data analysis technique using the percentage formula and product moment correlation and coefficient of determination. Based on the result of this study, it could be concluded that: (1) self-confidence of 10th grade students of Panca Bhakti Vocational High School Kubu Raya was classified â€œhighâ€, (2) the social interaction of 10th grade students of Panca Bhakti Vocational High School Kubu Raya was classified â€œgoodâ€, (3) there is significant influence of the social interaction of 10th grade students of Panca Bhakti Vocational High School Kubu Raya.Â Â Keywords: Self-Confidence, Social InteractionÂ Â